Synthesis, characterization, electrochemical and molecular docking studies of ternary metal (ii) complexes with schiff base ligand and 1,10-phenanthroline - G. SASIKUMAR; A. ASHMA; A. SUBRAMANI; S.J. ASKAR ALI (International Journal of Pharma and Bio Sciences, 2018)
In an attempt to develop effective bioactive mixed ligand Co(II), Ni(II), Cu(II) and Zn(II) metal complexes of type [M(L)(phen)] 1-4 where L is potassium (E)-2-((5-bromo-2-hydroxybenzylidene)amino)acetate which is derived from 5-bromosalicylaldehyde and glycine, and phen = 1,10 phenanthroline as a co-ligand. The newly synthesized metal(II) complexes were successfully isolated and characterized by using FT-IR, UV-Visible, ESI-Mass and cyclic voltammetry techniques. The Schiff base (ONO donor) coordinated to the central metal ion via azomethine nitrogen, phenolic oxygen and carboxylate ion in the axial mode, whereas, 1,10-phenanthroline displays bidentate (NN donor) mode of binding in the equatorial position. The stoichiometric nature of all the synthesized metal(II) complexes were found to be monomeric (1: 1: 1) with distorted square pyramidal geometry. The proposed structure of metal(II) complexes more evidently supported by ESI-Mass spectrometry. Moreover the electrochemical data suggests that irreversible one electron transfer process involved in all the metal(II) complexes. The oxidation potential values for Co(II), Ni(II) and Cu(II) complexes lies in in the region between +1.26 V and +1.28 V. Similarly, the reduction potential values lies in the region between -0.61 V and -0.69 V. Furthermore the molecular docking studies helped in understanding various mode of interaction of metal(II) complexes with TrkA receptor. All the complexes are located in the active site of the trkA kinase receptor. The complexes 1, 2, 3 and 4 showed the binding energy values of –8.61, –8.72, –8.84 and –8.47 kcal/mol with one, two, two and two hydrogen bond interactions, respectively. Among all the complexes docked, 3 showed the lowest binding energy value of –8.84 kcal/mol.